2018
DOI: 10.1007/s00122-018-3086-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping for resistance to leaf rust, stripe rust and tan spot in wheat reveals potential candidate genes

Abstract: Key messageGenome-wide association mapping in conjunction with population sequencing map and Ensembl plants was used to identify markers/candidate genes linked to leaf rust, stripe rust and tan spot resistance in wheat.AbstractLeaf rust (LR), stripe rust (YR) and tan spot (TS) are some of the important foliar diseases in wheat (Triticum aestivum L.). To identify candidate resistance genes for these diseases in CIMMYT’s (International Maize and Wheat Improvement Center) International bread wheat screening nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 144 publications
(151 reference statements)
4
86
0
Order By: Relevance
“…Chromosome 4A appears to be an important genome region with a high potential for leaf rust resistance in wheat. Correspondingly, promising loci were previously detected in association studies observing adult plant resistance in a set of American spring wheat (Gao et al 2016) and in a diverse core set including winter and spring wheat (Li et al 2016) or considering seedling resistance in a wheat collection of CIMMYT (Juliana et al 2018). The detected single nucleotide polymorphism (SNP) BobWhite_c47168_289 (SNP332) was also found as significantly associated with leaf rust resistance on wheat chromosome 4A by Gao et al (2016).…”
Section: Specific Hybrid Combinations Outperformed Parental Lines Formentioning
confidence: 87%
See 1 more Smart Citation
“…Chromosome 4A appears to be an important genome region with a high potential for leaf rust resistance in wheat. Correspondingly, promising loci were previously detected in association studies observing adult plant resistance in a set of American spring wheat (Gao et al 2016) and in a diverse core set including winter and spring wheat (Li et al 2016) or considering seedling resistance in a wheat collection of CIMMYT (Juliana et al 2018). The detected single nucleotide polymorphism (SNP) BobWhite_c47168_289 (SNP332) was also found as significantly associated with leaf rust resistance on wheat chromosome 4A by Gao et al (2016).…”
Section: Specific Hybrid Combinations Outperformed Parental Lines Formentioning
confidence: 87%
“…Table 4). The importance of chromosome 2A for seedling and adult plant resistance in wheat was also shown by Juliana et al (2018) considering CIMMYT´s bread wheat pool. Positions of detected loci on 2A are in coincidence with previous detected NBS-LRR genes (IWGSC 2018).…”
Section: Specific Hybrid Combinations Outperformed Parental Lines Formentioning
confidence: 89%
“…Juliana et al. () reported that the lines in CIMMYT breeding populations had a complex structure, which was difficult to define due to the intensive breeding history including a large number of sister lines and closely related lines along with introgressions of unrelated materials. The different population structure from I9K was likely due to the lack of markers in some important regions determining the subtle population differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To dissect the genetic basis of traits through GWAS, several studies were conducted using array-based platforms (Liu, Pinto, Cossani, Sukumaran, & Reynolds, 2019;Lopes, Dreisigacker, Pena, Sukumaran, & Reynolds, 2015;Sukumaran, Dreisigacker, Lopes, Chavez, & Reynolds, 2015, 2018bValluru, Reynolds, Davies, & Sukumaran, 2017) in spring wheat and sequencing-based platforms (Sukumaran, Reynolds, & Sansaloni, 2018c) in durum wheat (Triticum durum Desf.). Genomic prediction studies were also conducted using the I90K and DArTseq platforms (Christy et al, 2018;Crossa et al, 2014Crossa et al, , 2016aCrossa et al, , 2016bCrossa et al, , 2017Juliana et al, 2018Juliana et al, , 2019Rutkoski et al, 2016;Sukumaran, Crossa, Jarquin, Lopes, & Reynolds, 2017a, 2017b.…”
Section: Introductionmentioning
confidence: 99%
“…One hundred-twenty consistent loci were detected using SNP-GWAS and Haplotype-GWAS, and 78 were potentially new [28]. The recently released reference genome sequence of Chinese Spring [29] provides an elit platform for detecting genes significantly associated with linked markers with known physical positions in the genome and promoting the molecular breeding process [30]. In this study, we report a GWAS analysis of FHB resistance using a set of 171 common wheat cultivars with 90 K SNP genotyping and 2 year's phenotyping data.…”
Section: Introductionmentioning
confidence: 99%